International review of neurobiology. - Bradley, Ronald J.; Harris, R. Adron (International review of neurobiology, 1995)
Published since 1959, this serial stays up-to-date with current topics in neuroscience; the contributors are first-class experts in their fields. Volume 38 of International Review of Neurobiology presents in-depth reviews on GABAA and other transmitter systems and mechanisms, the genetics of the basal ganglia, the Bergmann glial cell, and the modes of action of monoamines at the cellular level. Neuroscientists will find particularly useful the recent studies on the molecular biology of neurotransmitter transporters. Key Features * Structure, pharmacology, and regulation of GABAA * Bergmann glial cell physiology * Abnormalities of transmitter systems in schizophrenia * Research in genetic influences on the basal ganglia * Presynaptic electrophysiology measurements Monoamines as stimulators and inhibitors of cellular mechanisms * Molecular biology of neurotransmitter transporters.